Linguistic Passing and Racial Identity Performance in Brit Bennett's The Vanishing Half: A Sociolinguistic Reading - Wahyu Utama; Friza Youlinda (Educational Journal, 2026)
This study examines the representation of linguistic passing and racial identity performance in Brit Bennett's The Vanishing Half through a sociolinguistic perspective. Employing a qualitative research design with a close reading approach, the study analyzes dialogues, narrative descriptions, and communicative practices related to language use, accent, register, and strategic silence. The analysis is informed by Bucholtz and Hall's sociocultural linguistic framework, particularly the concepts of identity emergence and indexicality, as well as Irvine and Gal's theory of language ideology. The findings reveal that linguistic passing is a gradual process through which racial identity is continuously constructed and negotiated rather than an instantaneous transformation. Stella's identity is maintained through deliberate adjustments in speech style, register, accent, and strategic silence, enabling her to conform to the linguistic expectations of White society. The study further demonstrates that language functions as a primary resource for constructing social identity, while language ideology shapes how linguistic features are interpreted within specific social contexts. These findings contribute to sociolinguistic literary criticism by highlighting that racial identity in the novel is produced not only through physical appearance but also through everyday linguistic practices, emphasizing the central role of language in identity performance.